Optoelectronic transceivers development platform: XFP implementation OLT NG-PON2 - Marques, Samuel de Jesus (2021)
Over the recent past, there has been a clear evolution in the development and implementation of fiber optics to the end user. FTTH networks were developed and standardized across the world, but the bandwidth requirements by users and services demanded by this technology evolved, from GPON to XG-PON, and now to NG-PON2. For the next generation optical components, it is relevant to create solutions that allow the testing and calibration of these components, however this is only possible if a manual sweep of the parameters is carried out in a first phase, which will be done in this dissertation. In this work, some optical transceivers are presented and several tests for characterizing transmitters and receivers were performed, intended to be implemented in a OLT XFP for NG-PON2. With this dissertation, it was possible to conclude that both the transmitter and the receiver tested present results compliant to the commercial ones, and which regards the figures of merit addressed, they meet the requirements of ITU-T G.989.2 standards. This leaves good prospects for the development of an OLT XFP compliant and low cost by PICadvanced, SA.